Legal Uncertainty in the Criminal Liability of Health Workers: A Normative Analysis of Article 440 of the Health Law and Article 360 of the Criminal Code - Maryanto; Abdul Kolib; Handar Subhandi Bakhtiar (International Journal of Social Sciences and Humanities, 2026)
Article 440(1) of Law Number 17 of 2023 on Health introduces a specific provision governing the criminal liability of health workers for medical negligence resulting in serious injury. Nevertheless, Supreme Court Decision Number 1241 K/Pid/2025 demonstrates that courts continued applying Article 360(1) of the Criminal Code despite the prosecutor’s indictment under Article 440. This study analyses the normative relationship between both provisions and its implications for legal certainty in medical negligence cases. The research employs a normative juridical method using statutory, conceptual, and case approaches. The findings show that the district court, high court, and Supreme Court consistently relied on Article 360 of the Criminal Code in convicting a nurse who performed circumcision without a practice licence outside an authorised health facility, causing permanent injury to a child patient. The judgments did not adequately address the applicability of Article 440 as a specific provision concerning medical negligence. The study identifies conflicts, overlaps, and vagueness of norms that contribute to inconsistent judicial interpretation. Therefore, clearer legislative formulation and Supreme Court guidelines are required to ensure legal certainty and consistency in adjudicating medical negligence cases involving health workers.